Synthetic studies on Stemona alkaloids. Construction of the sessilifoliamides B and C and 1, 12-secostenine skeleton. Issue 24 (16th June 2016) - Alonso-Fernández, Javier; Benaiges, Cristina; Casas, Eva; Alibés, Ramon; Bayón, Pau; Busqué, Félix; Álvarez-Larena, Ángel; Figueredo, Marta
Abstract: An original synthetic approach to the Stemona alkaloids stenine and sessilifoliamides B and C has been explored. The strategy relies on the early construction of the pyrroloazepine core (rings A and B) and latter addition of the furanone (ring D) and ethyl chain at C-10, which are the common structural features of the three alkaloids. The formation of the azabicyclic nucleus through an intramolecular Morita–Baylis–Hillman reaction of a properly substituted pyrrolidone has been extensively investigated by modifications on the substrate and all the parameters involved in the process and an efficient protocol in terms of yield and stereoselectivity has been developed. Despite many alternative tactics were explored, insurmountable difficulties found in the last synthetic steps have frustrated the completion of the syntheses. However, along the way, a plethora of new compounds was prepared, some of them containing the full skeleton of the targeted alkaloids, which can be useful for future synthetic applications. Graphical abstract: